THE EFFECT OF SOCIAL MEDIA UTILIZATION, CAMPUS ENVIRONMENT AND ENTRE-PRENEURSHIP KNOWLEDGE ON STUDENT ENTREPRENEURIAL INTEREST - Lesmana, Indra; Purwana, Dedi; Rachmadania, Rizki Firdausi (Faculty of Economics and Business, Universitas Negeri Jakarta, 2023)
The purpose of this study was to determine the effect of the use of social media, campus environment and entrepreneurial knowledge on interest in entrepreneurship in students of the Faculty of Economics, Jakarta State University class of 2017 and 2018. The research method used was a survey method with a descriptive approach, the population used was university students. Education Faculty of Economics, Jakarta State University class 2017 & 2018 with a sample of 266 students. The model in this study uses a path analysis model. The analytical technique used in this study uses multiple linear regression analysis with SPSS for hypothesis testing.